Factors related to non-adherence to the realization of the Papanicolaou test - Márcia Aparecida dos Santos Silva; Érica Mairene Bocate Teixiera; Rosangela Aparecida Pimenta Ferrari; Maria Elisa Wotzasek Cestari; Alexandrina Aparecida Maciel Cardelli (Universidade Federal do Ceará, 2015)
Objective: to identify reasons for low adherence to the Papanicolaou test in women seeking care in primary health care. Methods: cross-sectional study. Data collection carried out during home visits, applying questionnaire to characterize sociodemographic aspects as well as the reasons for non-adherence to examination and suggestions for facilitating adherence. Results: among 169 women, 67% were of reproductive age and 73.9% have finished elementary school. The failure to previously scheduled examination was due mainly to the beliefs and attitudes (36.1%) and service organization (25.4%). The feelings reported by women during the Papanicolaou test were shame (55.6%), discomfort (32.5%) and pain (20.7%). Conclusion: Although the screening of cervical cancer is essential for timely intervention, a significant proportion of women still does not adhere to examination by myths and taboos, beliefs, and health attitudes, as well as service organization.